KARAKTERISTIK MUTU ORGANOLEPTIK AYAM PANIKI YANG DIKEMAS DENGAN PROSES PENGALENGAN - Husen, Janiah; Bahri, Syamsul; Rasulu, Hamidin (Jurnal Pertanian Khairun, 2023)
Traditional food often has a short shelf life problem and is only able to maintain shelf-life quality for 24 hours at room temperature. North Maluku also has a variety of traditional specialties, one of which is chicken panici. Paniki chicken contains quite high levels of water and oil/fat so it has a short shelf life. The principle of packaging with retort cans is sterilization to kill spoilage microbes and pathogens by heat at a certain time and temperature. This research aims to determine the effect of sterilization time on the organoleptic quality of panici chicken in canned packaging. The research design used was a completely randomized design with 4 treatments and 3 replications. Treatment variations include sterilization time, namely W1 = 10 minutes, W2 = 15 minutes, W3 = 20 minutes, and W4 = 25 minutes. Organoleptic quality analysis data was analyzed using ANOVA with a significance level of 5% and Advanced Test using BNT. Based on the results of observations and discussion descriptions which are limited to the scope of this research, the sterilization time treatment has a significant effect on organoleptic parameters with the parameters of color, aroma, texture and taste of canned panicled chicken. And the sterilization time is 25 minutes to produce canned chicken panici of the best quality based on organoleptic criteria (color, aroma, texture and taste) which are still acceptable.Keywords: traditional food, chicken panicle, canning, sterilization